PERKEMBANGAN BAHASA PADA ANAK DALAM PSIKOLOGI SERTA IMPLIKASINYA DALAM PEMBELAJARAN - Erisa Kurniati (Universitas Batanghari Jambi, 2017)
The development is the product of the process of biological, cognitive, and sosioemosional, which are often intertwined. Development of the period include infants, children of early, middle and late, teen, and adult beginning. Jean Piaget's theory of cognitive development of children which involves important processes: schemes, assimilation, accommodation, organization, ekuilibrasi. In theory, of cognitive development occurs in the sequence of the four stages, namely remote motor (from birth up to the age of 2 years), pre-operational (3-7 years), concrete operational (7-11 years), and formal operational (11-15 years). At each stage of the qualitative progress. On the other hand, Lev Vygotsky suggested theories about the development of cognitive. Vygotsky stressed that cognitive skills need to be interpreted in developmental,mediated by language, and have the origins of social relations and culture. Theory of cognitive development Bruner stated a person characterized by increasing variation in the response to the stimulus. Where a person's cognitive development evolved from the enaktif to the iconic stage and ultimately to the symbolic. Related to this, Chomsky stated that the language was a form of communication, whether it be oral,written or sign, which is based on a system of symbols. Biologically, the children prepared to learn a language when they interact with their environment. As for the mastery of the language will experience a development in line with the development ofthe individual itself is influenced by biological factors and environmental factors.Keywords: Children's Language Development, Psychology, Learning